Impact of nutritional routine and training methods used by Sri Lankan national taekwondo players for weight loss prior to competition - Meegoda, D. K.; Perera, S. H.; Perera, S.; Linganathan, S. (British Journal of Sports Medicine, 2021)
Objective To determine the weight control strategies used by Sri Lankan national Taekwondo players who were in the SAG (South Asian Games) pool 2020.